Actualización del programa de protección contra caídas en actividad de pilotaje tipo Kelly - Murillo Murcia, Jenny Lisney; Jimenez Amado, Carmen Susana (Corporación Universitaria Minuto de Dios., 2022)
The purpose of this work is to update the program against falls of the Kelly-type piloting activity in the construction sector, with the current resolution 4272 of 2021, which establishes the minimum safety requirements for the development of work at heights. Whose field of application is to all employers, contractors, apprentices and workers of all economic activities that develop work at heights, this Kelly-type piling activity is mainly used in the construction of footings, foundation beams. This activity consists of mechanical drilling without coating, with the support of specialized tools such as; buckets, bits and others, the process begins with the introduction of the cover in the well, this cover has a reinforced tip which is in charge of drilling the ground and then putting the piles while the curvature advances in the drilling, the earth is removed from its interior with an auger, and as the drilling progresses, the collaborators descend to review and incorporate a new session, here already there is work at height with more than two meters of descent, which must have their respective equipment of protection against falls, this allows to control the process of drilling and extraction of rock according to the characteristics of the soil, then a mesh is placed that prevents collapses in the structure and then the concrete that finally forms the beams or footings of a large construction is placed.
Actualizar el programa de protección contra caídas conforme a los requisitos contemplados en la resolución 4272 de 2021 para actividades de pilotaje tipo Kelly.
Keywords: Pilotaje; Alturas,; Caída; Accidente; Piloting; Heights; Fall; Accident